Facillitating diabetes care - a community approach. Issue 1 (24th July 2013) - Goulder, Tim; Kar, Partha
Abstract: Instigated through the vision of a local GP, the South East Hampshire Community Diabetes Team (CDT) is provided by Southern Health NHS Foundation Trust. Through taking an integrated, multidisciplinary, community based specialist approach, the team works in partnership with colleagues across primary and secondary care. The team support care of both newly diagnosed people with diabetes (PWD), and those requiring ongoing follow up, unless they fall into the 'super six' categories. The key focus of the team is to optimise the knowledge and self management of diabetes through clinician and patient education programmes.